Efektivitas Penyerapan Anggaran Pada Dinas Pendidikan Dan Kebudayaan Kabupaten Aceh Barat - Salsabila; Yayuk Eko Wahyuningsih (CV ODIS, 2022)
This study aims to determine the level of effectiveness of the implementation of a budget there is an Education Office and Culture of West Aceh Regency. The scope taken by the author is the education budget for 2017 – 2022. The research analysis used is an analysis of effectiveness. research shows that the level or criteria for the effectiveness of budget absorption in the Education and Culture Office of West Aceh Regency in 201 7-2021 have varying effectiveness criteria. The highest level of effectiveness in 2017 and the lowest occurred in 2021. Furthermore, there were i017 criteria for effectiveness, from 2018 to 2021 criteria for effectiveness. This shows that the effectiveness of the budget implementation that has been budgeted has been well implemented by the Education Office and culture of West Aceh Regency, for a period of 5 (five) years from quite effective to very effective. To the Education office and culture of West Aceh Regency to continue to be able to maintain this achievement